MRI patterns indicate treatment success and tumor relapse following radiofrequency ablation of osteoblastoma - Kintzelé, Laurent; Brandelik, Simone Christine; Wünnemann, Felix; Weber, Marc-André; Lehner, Burkhard; Kauczor, Hans-Ulrich; Rehnitz, Christoph (International journal of hyperthermia and thermal therapies, 2020)
Purpose: To explore the typical magnetic resonance imaging (MRI) pattern of osteoblastoma (OB) after radiofrequency ablation (RFA) treatment and to identify signs indicating treatment success or relapse.Materials and methods: Forty-four follow-up MRI examinations of 15 patients with OB who had undergone 19 RFA procedures were analyzed retrospectively. An early follow-up group (1-4 months after RFA) and a late follow-up group (8-131 months after RFA) were established. The groups were further subdivided according to treatment success. Images were analyzed for the presence of central nidus enhancement (CNE), peripheral nidus enhancement (PNE), perifocal bone marrow edema (PBME) and fatty nidus conversion (FNC).Results: The early follow-up MRI image from every patient in the treatment success group exhibited a target-like appearance with negative CNE and positive PNE or PBME. PNE and PBME were observed in 93% and 71% of the early follow-up images, respectively. A target-like appearance was observed in 25% of the late follow-up images, and PNE and PBME were each observed in 20% of these images. FNC was not observed in the early follow-up images, but was seen in 55% of the late follow-up images. All three MRI images of the patients exhibiting clinical recurrence demonstrated strong CNE, PNE and extensive PMBE, which was in contrast to the images of the patients exhibiting treatment success.Conclusion: A target-like appearance of OB in early follow-up MRI examination indicates treatment success. PNE and PBME typically reduce over time and can lead to FNC in successfully treated patients. CNE recurrence, PNE and extensive PBME are signs of relapse.
Gesehen am 09.04.2020